2013
DOI: 10.1155/2013/870468
|View full text |Cite
|
Sign up to set email alerts
|

Heteropterys cotinifolia: A Neuropharmacological and Phytochemical Approach with Possible Taxonomic Implications

Abstract: Heteropterys cotinifolia (Malpighiaceae) has been used in traditional Mexican medicine mainly for the treatment of nervous disorders. However, the specific neuropharmacological activities responsible for this use remain to be defined. The present study evaluates the antidepressant and anxiolytic effects produced by the methanolic extract of Heteropterys cotinifolia and the influence of such effects on motor activity in ICR mice. Our results show that the methanolic extract of Heteropterys cotinifolia produces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The majority of the pharmacological literature reviewed here, showed that the neuroproperties are the bioactivities most studied in species from Heteropterys genus, following by antioxidant properties. Interestingly, mostly of these investigations that evaluated CNS activities comprise standardized extracts that partially reveal the chemical composition of the active extract: methanolic extract with presence of chlorogenic acid, chlorogenic acid methyl ester, and triterpene-type compounds in the case of H. brachiata for example (Huerta-Reyes et al, 2013a). In contrast, curiously the investigations that reveal the characterization of pure compounds obtained from extracts of the species of Heteropterys genus did not examined properties related with CNS but focused on other biological activities, such as antifungal, antimicrobial or antiviral (Junior et al, 2005;Melo et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the pharmacological literature reviewed here, showed that the neuroproperties are the bioactivities most studied in species from Heteropterys genus, following by antioxidant properties. Interestingly, mostly of these investigations that evaluated CNS activities comprise standardized extracts that partially reveal the chemical composition of the active extract: methanolic extract with presence of chlorogenic acid, chlorogenic acid methyl ester, and triterpene-type compounds in the case of H. brachiata for example (Huerta-Reyes et al, 2013a). In contrast, curiously the investigations that reveal the characterization of pure compounds obtained from extracts of the species of Heteropterys genus did not examined properties related with CNS but focused on other biological activities, such as antifungal, antimicrobial or antiviral (Junior et al, 2005;Melo et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…A study of a plant of the same family, Byrsonima crassifolia, showed that a methanolic extract that was standardized in flavonoid concentration presented an antidepressant effect in the FST and determined that the compounds responsible for the antidepressant effect were quercetin, quercetin 3-O-xyloside, and rutin [34]. On the other hand, a methanolic extract of Heteropterys cotinifolia (Malpighiaceae) was shown to have a dose-dependent antidepressant effect without reduction of spontaneous motor activity; the main compounds in this extract to which this pharmacological effect is attributed were chlorogenic acid and rutin [4]. A polyphenol-rich fraction of Origanum majorana L. containing luteolin-7-O-glucoside, kaempferol-3-O-glucuronic acid, kaempferol-3-O-pentose, quercetin, and rutin presented an antidepressant effect in the forced swimming test and tail suspension test [45].…”
Section: Discussionmentioning
confidence: 95%
“…We also performed the first phytochemical profile of this plant species. Several studies have been conducted with polar extracts and compounds isolated from plants of the Malpighiaceae family and have shown CNS-level anxiolytic, antidepressant, hypnotic, anticonvulsant, and antischizophrenic effects in several pharmacological tests [4,17,[32][33][34][35][36][37]. Some chemical compounds have been proposed to be responsible for these pharmacological effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been well documented that Hypericum perforatum, a "modern" herbal antidepressant, exerts extensive anti-inflammatory activities including the inhibitory activity on TNF-α, IL-1β, and LPS-induced prostaglandin E2 (Huang et al, 2011;Hammer and Birt, 2014). Recently, there is significant attention focused on the antidepressant-like effect of flavonoids extracted from herb medicines (González-Cortazar et al, 2013;Huerta-Reyes et al, 2013;Lv et al, 2014;Roohbakhsh et al, 2014;Reis et al, 2014), and it is notable that anti-inflammatory effect is also one of the primary biological activities of flavonoids (Tuñón et al, 2009;Shalini et al, 2012). Therefore, we may speculate that the anti-inflammatory effect of these herbs is possibly related to their antidepressant-like effect.…”
Section: Discussionmentioning
confidence: 99%